The Influence of Multicultural Services and Religious Background on Patient Satisfaction Through Employee Loyalty at Rosida Midwife Independent Practice, Purwakarta - Ainisyifa, Rina; Zaharuddin, Zaharuddin; Junaedi, Dudun (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of multicultural service and religious background on patient satisfaction through employee loyalty at Praktek Mandiri Bidan Rosida. This research uses a quantitative approach with a survey method conducted on respondents who have received services at the clinic. The population in this study consisted of all patients who had visited Praktek Mandiri Bidan Rosida, while the sample was determined using specific criteria of service recipients; however, the exact number of respondents is not specified in this abstract. Data were analyzed using path analysis to examine both the direct and indirect relationships among variables. The results show that multicultural service and religious background have a significant effect on patient satisfaction. Furthermore, patient satisfaction is proven to be a significant mediator in shaping patient loyalty. These findings highlight the importance of a service approach that respects cultural and religious diversity to enhance patient satisfaction and loyalty in midwifery care services.